Planning and practice of the Polish-Czech transborder road network development: From ineffective top-down plans to bottom-up lack of coordination? - Furmankiewicz, Marek; Buryło, Krzysztof; Dostál, Ivo; Hełdak, Maria; Lipsa, Joanna; Zathey, Maciej (European Spatial Research and Policy, 2025)
In this article, the authors analyse the development policy of the major road network in the Polish-Czech border areas in 1958–2024. The methodology of content analysis covering historical bilateral and European planning documents and GIS spatial analysis of access to border areas via roads crossing the border. The analyses have shown: (1) dominance of political and expert planning, without the use of scientific network models; (2) decentralisation of planning and resignation from common documents; (3) prioritising east-west connections and disregarding the north-south European ones; and (4) the greatest increase in border permeability only after the elimination of permanent border controls within the EU Schengen Area since 2007, but mainly due to the opening of historical roads.